2014
DOI: 10.1016/j.bbadis.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines downregulate Hsp27 and cause apoptosis of human retinal capillary endothelial cells

Abstract: The formation of acellular capillaries in the retina, a hallmark feature of diabetic retinopathy, is caused by apoptosis of endothelial cells and pericytes. The biochemical mechanism of such apoptosis remains unclear. Small heat shock proteins play an important role in the regulation of apoptosis. In the diabetic retina, pro-inflammatory cytokines are upregulated. In this study, we investigated the effects of pro-inflammatory cytokines on small heat shock protein 27 (Hsp27) in human retinal endothelial cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…37 Similar findings were reported immediately after retinal injury. In our animal model of light-induced retinal degeneration, photoreceptor apoptosis was clearly observed in both histologic images and immunofluorescent TUNEL staining images.…”
Section: Discussionsupporting
confidence: 70%
“…37 Similar findings were reported immediately after retinal injury. In our animal model of light-induced retinal degeneration, photoreceptor apoptosis was clearly observed in both histologic images and immunofluorescent TUNEL staining images.…”
Section: Discussionsupporting
confidence: 70%
“…VEGF also played a role on inducing endothelial cell death after oxygen-glucose deprivation (46). Our previous studies (16,6265) and many others (6668) have demonstrated that high glucose increased the levels of apoptosis in REC. We showed that miR-146a played a role in reducing REC apoptosis under high glucose conditions by decreasing the levels of DNA fragmentation.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast to this degenerative effect, several studies demonstrated that HSP27 prevented the degeneration of neuronal cells through stabilization of the actin cytoskeleton or the suppression of apoptotic stimuli [22,35]. In addition, the downregulation of HSP27 led to apoptosis of human retinal endothelial cells [36]. Hence, HSP27 can demonstrate degenerative and protective effects in different models or conditions.…”
Section: Ganglion Cell Loss Did Not Affect the Total Retinal Structurementioning
confidence: 99%